Pendampingan Penulisan Artikel Ilmiah bagi Komunitas Guru Sekolah Dasar Melalui Service Learning Approach di Kecamatan Sukun Kota Malang - Ifit Novita Sari; Dwi Fita Heriyawati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
One of the rarely trained skills of the teachers in writing scientific papers. The reason is that the teachers are less trained to write a scientific article. Currently, scientific articles are one of the mandatory requirements for promotion for teachers. This community service activity is intended to assist teachers in writing scientific articles based on the results of classroom action research (PTK) that has been carried out. The method was conducted through workshops, discussions, questions and answers, face-to-face guidance services, and e-mail. The results indicated a paradigm shift in writing scientific articles. Initially, the teachers experienced difficulties, but after the training, they felt easy because they already knew how to put the ideas of the CAR (PTK) results in article writing. The results indicate that with further instruction and guidance, the teachers’ capacity improves and the drafts were good with some improvement The articles will then published in accredited journals for the teachers’ promotion.